Hybrid prosthesis: a literature review - Nina Permatasari; Irfan Dammar (Makassar Dental Journal, 2020)
The loss of teeth is a problem that often causes mastication, phonetic, and esthetic interferences. The use of removable partial denture (RPD) with clasp is often unsatisfactory for patients from functional and aesthetic aspects. Retention and stabilization must be considered in making RPD. In the case of free-end dentures, which fixed dentures (FD) is contraindicated, another option is a hybrid prosthesis that combines a RPD with FD using precision attachment. Clasp used as denture retention can be replaced with precision attachment to produce better retention.